The power of nonviolence - Gregg, Richard Bartlett 1885-1974; Tully, James 1946- (Cambridge texts in the history of political thought, 2018)
"Richard Gregg's The Power of Nonviolence (PNV) is one of the most important and influential texts in the history of nonviolence. It is even more important today as many aspects of Gregg's philosophy have stood the test of practice and time. It is a classic"...